Faktor-Faktor Yang Berhubungan Dengan Ketidaktahuan Ibu Tentang Tanda Bahaya Risiko Kehamilan - yuyun priwahyuni (STIKes Hang Tuah Pekanbaru, 2017)
Based on the data from the Basic Health Research (Riskesdas, 2012) stated that only 44% of expectant mothers who knew about the danger signs of pregnancy. Several factors that influence the ignorance of the mother of a danger sign of the pregnancy is education, a job, age, interest, experience, culture the surrounding environment, and information. On the other hand, there were only 23% of the complicated cases that got the health care services. Based on the data from City Health Care Department of Pekanbaru in January – March 2014 showed that there were 24.964 of expectant mothers who visit the Community Health Centre in Pekanbaruand there were 1.194 of them who were indicated as high-risk pregnancy. The Community Health Centre in Rumbaihad the highest number of it, there were 238 cases (19%) from 1.196 expectant mothers. This research aimed to know the factors related to the ignorance of expectant mothers about high-risk pregnancy in RumbaiPekanbaru year 2015. This research uses quantitative analytic with cross sectional design. The data are collected by using questionnaire. The population in January-March 2014 was 1.196 expectant mothers who were indicated as high-risk pregnancy and the sample are 160 expectant mothers, by using Purposive Sampling technique. The analysis used in this research is univariat analysis to discover the frequency of distribution and bivariate analysis by using chi-square. to see the relationship variable devenden and variable indevenden The result showed that there is a correlation between the age and mothers’ cognition about the risks in pregnancy (p value = 0,0001, POR 20,8), job and mothers’ cognition about the risks in pregnancy (p value = 0,0001, POR 134,7), source of information and mothers’ cognition about the risks in pregnancy (p value = 0,0001, POR 0,120), experience and mothers’ cognition about the risks in pregnancy (p value = 0,0001, POR 0,052). Based on the research, can be suggested that the mothers’ cognition need to be improved by doing counseling and spreading information about the danger signs of pregnancy in Community Health Centre Rumbai. Keywords : ignorance, danger signs of pregnancy, Community Health Centre Rumbai